Cardiopulmonary dysfunction in patients with limb‐girdle muscular dystrophy 2A. Issue 4 (30th December 2016) - Mori‐Yoshimura, Madoka; Segawa, Kazuhiko; Minami, Narihiro; Oya, Yasushi; Komaki, Hirohumi; Nonaka, Ikuya; Nishino, Ichizo; Murata, Miho
ABSTRACT: Introduction : Little is known about the frequency of cardiopulmonary failure in limb‐girdle muscular dystrophy type 2A (calpainopathy) patients, although some studies have reported severe cardiomyopathy or respiratory failure. Methods : To clarify the frequency of cardiopulmonary dysfunction in this patient population, we retrospectively reviewed the respiratory and cardiac function of 43 patients with calpainopathy. Results : Nine of the 43 patients had forced vital capacity (FVC) < 80%, and 3 used noninvasive positive pressure ventilation. Mean FVC was significantly lower in patients who were nonambulant and had normal creatine kinase levels. Only 1 patient had a prolonged QRS complex duration. Echocardiography revealed that 1 patient had very mild left ventricular dysfunction. Conclusions : These findings suggest that patients with calpainopathy may develop severe respiratory failure, but cardiac dysfunction is infrequent. Muscle Nerve 55 : 465–469, 2017